Development Analysis of Global Competitiveness Index of ASEAN-7 Countries and Its Relationship on Gross Domestic Product - Tongam Sihol Nababan (Fakultas Ekonomi, Universitas Bangka Belitung, 2019)
The objectives of the research are: (1) to investigate the development of global competitiveness index (GCI) of ASEAN-7 countries as an illustration of economic performance and potentiality, (2) to investigate which factors or pillars are drivers for the improvement of GCI ASEAN-7 countries, and (3) to analyze the effect of Gross Domestic Product (GDP) on GCI of ASEAN-7 countries. The analysis method used in calculating the weight of the contribution of each pillar to changes in the competitiveness index, and determining the effect of GDP on GCI, a Semi-Logarithmic Regression analysis is used. The result shows that during the period of year 2008/2009 to the year of 2016/2017, the rank and index of GCI of each ASEAN-7 countries continue to increase. The pillars of the basic requirement subindex still dominate the largest contribution to the improvement of the competitiveness index for Indonesia, Philippines, Thailand, Cambodia, and Vietnam. As for Malaysia and Singapore sub-indexes of efficiency enhancers and innovation-sophistication have been able to give the largest contribution to the improvement of GCI. The GDP of ASEAN-7 countries has a positive and significant impact on the improvement of global competitiveness index, except for Thailand. The most problematic factors in improving the competitiveness index are corruption, inadequately educated labour, access to financing, tax regulations, and inefficient government bureaucracy.